2021
DOI: 10.1177/00222437211002196
|View full text |Cite
|
Sign up to set email alerts
|

Heart or Mind? The Impact of Power Distance Belief on the Persuasiveness of Cognitive Versus Affective Appeals in Education Marketing Messages

Abstract: One of the greatest challenges in education marketing is designing effective marketing messages, especially when targeting consumers with different cultural backgrounds. This research examines the impact of power distance belief (PDB) on the persuasiveness of affective appeal versus cognitive appeal in education marketing messages. The authors theorize that low-PDB consumers tend to prefer education products presented with affective appeal because of their process learning mindset that focuses on self-discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 59 publications
0
21
0
1
Order By: Relevance
“…Lastly, this study also contributes to the growing literature on PDB by identifying its effect on novel consumer behavior (i.e., reliance on alignable attributes). It has been shown that PDB can influence various consumer behaviors such as status consumption (Gao et al, 2016), charitable behavior (Han et al, 2017; Winterich & Zhang, 2014), price sensitivity (Lee et al, 2020), attitudes toward celebrity endorsements (Winterich et al, 2018), and preference for advertising appeals (Tu et al, 2022). This study contributes to this PDB literature by demonstrating that high (low) PDB individuals are less (more) likely to be cognitively flexible, which, in turn, means that they are more likely to rely on alignable (nonalignable) attributes when evaluating products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, this study also contributes to the growing literature on PDB by identifying its effect on novel consumer behavior (i.e., reliance on alignable attributes). It has been shown that PDB can influence various consumer behaviors such as status consumption (Gao et al, 2016), charitable behavior (Han et al, 2017; Winterich & Zhang, 2014), price sensitivity (Lee et al, 2020), attitudes toward celebrity endorsements (Winterich et al, 2018), and preference for advertising appeals (Tu et al, 2022). This study contributes to this PDB literature by demonstrating that high (low) PDB individuals are less (more) likely to be cognitively flexible, which, in turn, means that they are more likely to rely on alignable (nonalignable) attributes when evaluating products.…”
Section: Discussionmentioning
confidence: 99%
“…As need for closure reduces cognitive flexibility (Kossowska et al, 2015), this finding suggests that individuals with high PDB may have lower cognitive flexibility. Similarly, Tu et al (2022) showed that individuals with high PDB tend to focus on the outcome, which also facilitates a quick conclusion, suggesting that individuals with high PDB are less cognitively flexible. Further, Lalwani and Forcum (2016) demonstrated that high PDB individuals are more likely to use price‐quality judgments, suggesting that such individuals would be less cognitively flexible.…”
Section: Conceptual Backgroundmentioning
confidence: 92%
“…This inclusive and expansive definition and scope of education is reflected in the content of this special issue, Although we discuss individual articles in detail subsequently, we draw attention to the fact that the content of this special issue spans a wide variety of educational avenues including K-12 education (Sen and Tucker 2022;Zhou, Gill, and Liu 2022), university education (Krishna and Orhun 2022), online education (Lu, Bradlow, and Hutchinson 2022;Narang, Yadav, and Rindfleisch 2022), and sales training (Singh, Sen, and Borle 2022). The content of this special issue also examines many different actors including students (Narang, Yadav, and Rindfleisch 2022), salespeople (Singh, Sen, and Borle 2022), curriculum development departments (Sen and Tucker 2022), grocery shoppers (Bollinger et al 2022), school administrators (Dolbec et al 2022), home tutors (Kim et al 2022), and buyers of educational products and services (Tu, Kwon, and Gao 2022). Consistent with our definition, this special issues touches on pedagogical content (Krishna and Orhun 2022;Sen and Tucker 2022), the process of gaining and imparting knowledge (Lu, Bradlow, and Hutchinson 2022;Narang, Yadav, and Rindfleisch 2022), and educational outcomes (Bollinger et al 2022;Goli, Chintagunta, and Sriram 2022;Singh, Sen, and Borle 2022).…”
Section: Education: Definition and Scopementioning
confidence: 99%
“…Specifically, a myopic focus can cause students to mistakenly forgo the higher long-term earning potential of attending a higher-quality institution for a shorter-term gain of lower loan expenses associated with a lower-tier institution. Bollinger et al (2022) and Tu, Kwon, and Gao (2022) explore the classic marketing problems associated with communication, investigating the effectiveness of marketing communications in realizing educational outcomes and the moderators of marketing communication's effectiveness. Using a case-study experiment involving product labeling in grocery stores in Canada, Bollinger et al find that campaigns designed to better educate consumers as to the nutritional value of foods through enhanced labeling indeed improve healthy consumption, but the beneficial effect is transitory.…”
Section: Articles In the Special Issuementioning
confidence: 99%
See 1 more Smart Citation